Mechanical behavior of laminated bamboo lumber dowel-type connection. Issue 1 (January 2020) - Li, Jiannan; Zhou, Aiping
Bamboo is a kind of green material with high specific strength, while the hollow tubular structure makes it rather hard to be utilized in structure. Glue and hot-pressing processes make laminated bamboo lumber rectangular cross section and with high strength properties. The dowel-type connection can be used in I-joist instead of the costly adhesive, while the behaviors of which are extremely complicated. European yield model is confirmed to be an effective method to estimate loading capacity of connection and is adopted by various standard and design codes. This article focused on a kind of connection innovatively with laminated bamboo lumber dowel. The embedment tests were carried out to study the embedment strength of laminated bamboo lumber members. Connection tests under lateral load were conducted to investigate the performance and loading capacity. Finally, theoretical results determined by design rules in current codes were compared with experimental results